Construction of microbial consortia for microbial degradation of complex compounds - Cao, Zhibei; Yan, Wenlong; Ding, Mingzhu; Yuan, Yingjin (Frontiers in Bioengineering and Biotechnology, 2022)
Increasingly complex synthetic environmental pollutants are prompting further research into bioremediation, which is one of the most economical and safest means of environmental restoration. From the current research, using microbial consortia to degrade complex compounds is more advantageous compared to using isolated bacteria, as the former is more adaptable and stable within the growth environment and can provide a suitable catalytic environment for each enzyme required by the biodegradation pathway. With the development of synthetic biology and gene-editing tools, artificial microbial consortia systems can be designed to be more efficient, stable, and robust, and they can be used to produce high-value-added products with their strong degradation ability. Furthermore, microbial consortia systems are shown to be promising in the degradation of complex compounds. In this review, the strategies for constructing stable and robust microbial consortia are discussed. The current advances in the degradation of complex compounds by microbial consortia are also classified and detailed, including plastics, petroleum, antibiotics, azo dyes, and some pollutants present in sewage. Thus, this paper aims to support some helps to those who focus on the degradation of complex compounds by microbial consortia.